2008
DOI: 10.1186/1752-1947-2-348
|View full text |Cite
|
Sign up to set email alerts
|

New onset neuromyelitis optica in a young Nigerian woman with possible antiphospholipid syndrome: a case report

Abstract: Introduction: Devic's neuromyelitis optica is an inflammatory demyelinating disease that targets the optic nerves and spinal cord. It has a worldwide distribution and distinctive features that distinguish it from multiple sclerosis. There has been no previous report of neuromyelitis optica from our practice environment, and we are not aware of any case associated with antiphospholipid syndrome in an African person.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 10 publications
0
12
0
Order By: Relevance
“…Despite abundant evidence linking TS and MS, only few reports have suggested their association with NMO 8,[18][19][20] . Wingerchuk 8 reported a TS incidence rate of 35% in patients with NMO (17 of 48 patients) and more recently, Usmani 19 reported an incidence of 14% (8 of 57 patients).…”
Section: Discussionmentioning
confidence: 99%
“…Despite abundant evidence linking TS and MS, only few reports have suggested their association with NMO 8,[18][19][20] . Wingerchuk 8 reported a TS incidence rate of 35% in patients with NMO (17 of 48 patients) and more recently, Usmani 19 reported an incidence of 14% (8 of 57 patients).…”
Section: Discussionmentioning
confidence: 99%
“…The spasms lasted a few seconds to minutes with a frequency varying around 2 to 15 times a day, consistent with previous descriptions. [1][2][3][4][5][6][7] None of the patients experienced a preictal aura, loss of consciousness, loss of sphincter control, or postictal sequele.…”
Section: Commentmentioning
confidence: 99%
“…Wingerchuk et al 6 reported a toxic spasms incidence rate of 35% in patients with relapsing-remitting NMO(17 of 48 patients). Komolafe et al 5 subsequently described a 28- year-old Nigerian woman with NMO who presented with neck pain, paroxysmal tonic spasms, and spastic quadriplegia. The observations by Wingerchuk et al and our own finding that paroxysmal tonic spasms are more common in NMO suggest that NMO be included in the differential diagnosis of such patients.…”
Section: Commentmentioning
confidence: 99%
“…Among the non‐organ‐specific autoimmune diseases are SLE, SS, antiphospholipid syndrome or sarcoidosis (class IV) [20,106–112]. Autoantibodies against nuclear antigens can be detected in NMO without clinical evidence of systemic autoimmune diseases.…”
mentioning
confidence: 99%